The Place of Broadcast Media and Opinion Leaders in Community Development - Micheal A. Nza-Ayang (PT FORMOSA CENDEKIA GLOBAL, 2024)
The main purpose of this research work is to find out the place of the mass media and opinion leaders in community development, using a study of Aniocha-North local government area of Delta State as a case in point. The method employed in gathering information for this study is the survey method of data collection using questionnaire and personal interview as primary sources while the use of journals, books, libraries, schools etc formed the secondary source of at collection. It was discovered that information from the mass media gets to members of Aniocha community through opinion leaders. Lazarfied and others said was true in Anicha community as it related to the community development of the town. Finally, since it is believed by the rural dwellers that mass media has not done any thing positive to change lives, the mass media should create the sense of identification through the propagation of common cultural value and symbol and by giving desirable interpretation of event.